Heat treatment process method for consistency of TC18 titanium alloy structure and performance

By using single-phase zone air-burning heat treatment and double annealing process in TC18 titanium alloy, the grain size is regulated, and the problem of unbalanced service performance of TC18 titanium alloy is solved, and the matching of high tensile strength and fracture toughness is achieved, which significantly improves the Consistency of component performance.

CN118186325BActive Publication Date: 2025-01-07CHINA NAT ERZHONG GRP DEYANG WANHANG DIE FORGING CO LTD +1

Patent Information

Application Number
CN202410521722.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-04-28
Publication Date
2025-01-07
Estimated Expiration
2044-04-28

AI Technical Summary

Technical Problem

In the prior art, the structure-service performance of TC18 titanium alloy cannot be balanced, and it is difficult to achieve high tensile strength, good plasticity and fracture toughness at the same time.

Method used

Double annealing is performed after a single-phase zone air-fired heat treatment process. By regulating the insulation temperature and time of the two-step heat treatment, the grain size is controlled to achieve a matching of high strength and high toughness.

Benefits of technology

While tensile strength is between 1110 and 1140MPa, the fracture toughness is not less than 70MPa·m1/2, which significantly improves the consistency of component performance of TC18 titanium alloy.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118186325B_ABST
    Figure CN118186325B_ABST
Patent Text Reader

Abstract

The invention discloses a TC18 titanium alloy organization service performance consistency heat treatment process method, belongs to the field of metal material heat treatment technology, which includes the following steps: the first step of heat treatment: single-phase zone heating, using TC18 titanium alloy, TC18 titanium alloy is kept at Tβ-40℃ for 1h according to the air burning heat treatment process, heated to [Tβ+15℃, Tβ+35℃] for 0-4h, and cooled to room temperature; the second step of heat treatment: double annealing, the cooled TC18 titanium alloy is heated to 820-850℃ for 1-3h and then furnace cooled, after furnace cooling, kept at 740-760℃ for 1-3h and then air cooled, after air cooling, kept at 600-620℃ for 2-6h and then air cooled to room temperature. The present invention selects different insulation temperatures and times, regulates the equiaxed α grain size of TC18 titanium alloy, and determines the heat treatment process parameters, so that the TC18 titanium alloy has both high tensile strength and good strength and fracture toughness.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of heat treatment of metal materials, and in particular relates to a heat treatment process method for achieving consistency in service performance of a TC18 titanium alloy structure. Background Art

[0002] The nominal composition of TC18 titanium alloy is Ti-5Al-5V-5Mo-1Cr-Fe. It is a highly alloyed α+β type titanium alloy with the advantages of high strength, high plasticity, high toughness and good welding performance. Therefore, it is widely used in the aerospace field. Using TC18 titanium alloy instead of high-strength steel in aircraft structural parts can reduce weight by 15-20%. At present, TC18 titanium alloy has been widely used in the preparation of main load-bearing structural parts such as large landing gear beams and fuselage docking frames. The main load-bearing components of some military transport aircraft, passenger aircraft, large transport aircraft and other models have been upgraded and replaced by TC18 titanium alloy. The amount of TC18 titanium alloy components in some models is as high as 3 tons. With the rapid development of aircraft models and large transport aircraft, the demand for high-performance TC18 alloy is becoming increasingly urgent.

[0003] Heat treatment process plays an important role in regulating the microstructure and mechanical properties of TC18 titanium alloy. The common heat treatment process of TC18 titanium alloy adopts double annealing or solution aging. Among them, the solution aging process can greatly improve the strength of TC18 titanium alloy, but its fracture toughness is reduced; double annealing is recommended according to relevant specifications, and its general process is: 820-850℃ insulation for 1-3h → furnace cooling to 740-760℃ insulation for 1-3h → air cooling → 500-650℃ insulation for 2-6h → air cooling. The double annealing process has better strength-toughness matching.

[0004] At present, the patent literature related to the heat treatment of TC18 titanium alloy mainly focuses on the control of the holding temperature and holding time of the solution aging process or double annealing treatment. For example, in a heat treatment method of TC18 titanium alloy (CN103924180A), the microstructure of the alloy is regulated by selecting the holding temperature, time and cooling method to achieve a good match between plasticity and toughness, but the maximum fracture toughness is only 61MPa·m1 / 2. A heat treatment method of TC18 titanium alloy with high fracture toughness (CN115725916A) also selects the holding temperature and time to regulate the microstructure of TC18 titanium alloy to achieve a good match between strength and toughness. Although the maximum fracture toughness is 97MPa·m1 / 2, the tensile strength is only 1056MPa. It can be seen that in the prior art, the service performance of the TC18 titanium alloy structure cannot be balanced. The service performance includes at least tensile strength, elongation and fracture toughness. Therefore, in order to make the TC18 titanium alloy components have both high tensile strength and good plasticity and relative balance of toughness, a heat treatment method is needed to make the service performance of the TC18 titanium alloy consistent. Summary of the invention

[0005] In view of the deficiencies in the prior art, the present invention provides a heat treatment process for consistency of service performance of TC18 titanium alloy tissue. Taking into account the particularity of the use occasions of TC18 titanium alloy, high requirements are placed on the stability of its component tissue and the consistency of performance, and the stability of the rod tissue largely determines the consistency of component performance. Therefore, the present invention aims at the matching relationship between the microstructure of TC18 titanium alloy rod and its service performance. First, TC18 titanium alloy rods with different grain sizes are obtained through a single-phase zone air-burning heat treatment process, and then double annealing heat treatment is performed to explore the effect of grain size on the service performance of TC18 titanium alloy components after double annealing. By adjusting the insulation temperature and insulation time of the two-step heat treatment process, a tensile strength of 1110-1140MPa and a fracture toughness of not less than 70MPa·m are obtained. 1 / 2 TC18 titanium alloy.

[0006] To achieve the above object, the present invention discloses a TC18 titanium alloy structure service performance consistency heat treatment process method, comprising the following steps:

[0007] The first step of heat treatment: single-phase zone heating;

[0008] TC18 titanium alloy is used as raw material. TC18 titanium alloy is a dual-phase titanium alloy composed of β phase and equiaxed α phase;

[0009] The TC18 titanium alloy is kept at Tβ-40°C for 1 hour according to the air-fired heat treatment process, the temperature is raised to [Tβ+15°C, Tβ+35°C] and kept for 0 to 4 hours, and then cooled to room temperature, wherein Tβ is the phase transition temperature point of the β phase of the titanium alloy;

[0010] The second step of heat treatment: double annealing;

[0011] The cooled TC18 titanium alloy obtained by the first step heat treatment is heated to 820-850°C and kept at that temperature for 1-3 hours, then furnace cooled, kept at 740-760°C for 1-3 hours after furnace cooling, then air cooled, kept at 600-620°C for 2-6 hours after air cooling to room temperature.

[0012] Preferably, the chemical composition of TC18 titanium alloy is: Ti-5Al-5Mo-5V-1Cr-1Fe.

[0013] Preferably, the volume fraction of the equiaxed α phase of the TC18 titanium alloy is 36%, and the average size is 3-8 μm.

[0014] Preferably, in the first step of heat treatment, the TC18 titanium alloy is kept at Tβ-40°C for 1 hour according to the air-fired heat treatment process, and then the temperature is raised to [Tβ+25°C, Tβ+35°C] and kept for 2 to 4 hours;

[0015] Preferably, the cooling to room temperature in the first step of heat treatment is performed by air cooling.

[0016] Preferably, the grain size of the equiaxed α-type TC18 titanium alloy after the first step heat treatment is between 200 and 430 um.

[0017] Preferably, the grain size of the equiaxed α-type TC18 titanium alloy after the first step heat treatment is between 300 and 430 um.

[0018] Preferably, the service properties include tensile strength, elongation and fracture toughness.

[0019] Preferably, the TC18 titanium alloy obtained after the second step heat treatment has a tensile strength of 1110-1140 MPa, an elongation of 11-14%, and a fracture toughness of 70-80 MPa·m 1 / 2 .

[0020] Compared with the prior art, the present invention has the following beneficial effects:

[0021] 1. The present invention selects TC18 titanium alloy whose initial structure is equiaxed α phase + β phase, and controls the size of the α phase by adjusting the holding temperature and holding time of the heat treatment process, thereby obtaining a TC18 alloy with high strength and high toughness.

[0022] 2. The present invention reasonably controls the holding temperature and holding time of the first step of heat treatment and controls the size of the α phase, so as to ensure that the plasticity and toughness of the alloy meet the requirements; in the second step of heat treatment, the holding temperature and holding time are appropriately increased to improve the strength of the alloy. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 This is a microstructure morphology diagram of the original structure of the TC18 titanium alloy bar of the present invention;

[0024] Figure 2 is a microstructure morphology of the TC18 titanium alloy after two-step heat treatment in Example 1 of the present invention;

[0025] Figure 3 is a microstructure morphology of the TC18 titanium alloy after two-step heat treatment in Example 2 of the present invention;

[0026] Figure 4 is a microstructure morphology of the TC18 titanium alloy after two-step heat treatment in Example 3 of the present invention;

[0027] Figure 5 This is a microstructure morphology diagram of the TC18 titanium alloy after conventional double annealing heat treatment in the comparative example of the present invention;

[0028] Figure 6 It is a curve diagram showing the variation of the grain size of the TC18 titanium alloy according to the present invention with the unidirectional zone temperature and the holding time;

[0029] Figure 7 is a graph showing the relationship between grain size and tensile strength of the TC18 titanium alloy of the present invention;

[0030] Figure 8 is a graph showing the relationship between grain size and elongation of TC18 titanium alloy of the present invention;

[0031] Fig. 9 It is a curve diagram showing the relationship between the grain size and fracture toughness of the TC18 titanium alloy of the present invention. DETAILED DESCRIPTION

[0032] The exemplary embodiments, features and aspects of the present invention will be described in detail below with reference to the accompanying drawings. The same reference numerals in the accompanying drawings represent elements with the same or similar functions. Although various aspects of the embodiments are shown in the accompanying drawings, the drawings are not necessarily drawn to scale unless otherwise specified.

[0033] The present invention proposes a TC18 titanium alloy structure service performance consistency heat treatment process method, which comprises the following steps:

[0034] The first step of heat treatment: single-phase zone heating.

[0035] TC18 titanium alloy is used as raw material, and its chemical composition is: Ti-5Al-5Mo-5V-1Cr-1Fe. TC18 titanium alloy is a dual-phase titanium alloy, and its microstructure consists of β phase and equiaxed α phase. The volume fraction of equiaxed α phase is 36%, and the average size is 3-8μm. The original microstructure morphology is as follows Figure 1 shown.

[0036] The TC18 titanium alloy is kept at Tβ-40℃ for 1h according to the air-fired heat treatment process, and the temperature is raised to [Tβ+15℃, Tβ+35℃] and kept for 0-4h, and then cooled to room temperature, preferably by air cooling; Tβ is the phase transition temperature of the β phase of the titanium alloy. Generally, the titanium alloy is in full β phase above Tβ, and gradually begins to transform from β phase to α phase below Tβ temperature. Usually, the Tβ value is between 800-1050℃, for example, Tβ is 1000℃, and Tβ+15℃ refers to 15℃ above the β phase transition point of the titanium alloy, that is, 1015℃. The phase transition temperature point Tβ of the β phase of the TC18 titanium alloy in this embodiment is 870±5℃.

[0037] The TC18 titanium alloy has an alpha grain size of 200 to 430 um after the first heat treatment. Preferably, the TC18 titanium alloy has an alpha grain size of 300 to 430 um after the first heat treatment. The grain size will affect the performance of the titanium alloy. Therefore, the grain size is controlled by adjusting the holding temperature and holding time of the heat treatment process to obtain a TC18 alloy with high strength and high toughness.

[0038] The second step of heat treatment: double annealing.

[0039] The cooled TC18 titanium alloy obtained from the first step heat treatment is heated to 820-850°C and kept for (1-3) hours, then furnace cooled, kept at 740-760°C for (1-3) hours after furnace cooling, then air cooled, kept at 600-620°C for (2-6) hours after air cooling, and then air cooled to room temperature.

[0040] The service properties of the present invention include tensile strength, elongation, and fracture toughness. The TC18 titanium alloy obtained by the present invention has a tensile strength of 1110-1140 MPa, an elongation of 11-14%, and a fracture toughness of 70-80 MPa·m 1 / 2 .

[0041] The TC18 titanium alloys in Examples 1-3 all use TC18 titanium alloy bars of the same specifications.

[0042] Example 1

[0043] A sample with a size of Φ300×30mm was used. According to the air-fired heat treatment process, the sample was kept at Tβ-40℃ for 1h, heated to Tβ+15℃ for 0-4h, cooled to room temperature, and the α grain size was counted. Then the sample was heated to 840℃ for 2h and furnace-cooled. After furnace cooling, it was kept at 750℃ for 2h and air-cooled. After air cooling, it was kept at 620℃ for 4h and air-cooled to room temperature. The microstructure of the TC18 titanium alloy obtained after the two-step heat treatment is as follows: Figure 2 .

[0044] The α grain sizes corresponding to different holding times of the TC18 titanium alloy rod treated in this embodiment are shown in Table 1.

[0045] Table 1 α grain size corresponding to different holding time of TC18 rod in Example 1

[0046] Insulation time / h α Grain size / um 0.5h 190.2 1h 230.5 2h 279.4 4h 350.2 8h 430.1

[0047] The room temperature mechanical properties parameters corresponding to different α grain sizes of the TC18 titanium alloy rod treated in this embodiment are shown in Table 2.

[0048] Table 2 Room temperature mechanical properties of TC18 rods with different α grain sizes in Example 1

[0049] α Grain size / um Tensile strength / MPa Elongation / % <![CDATA[Fracture toughness / Pa·m 1 / 2 > 190.2 1098.3 14.1 75.2 230.5 1118.3 11.9 72.3 279.4 1135.1 11.1 69.8 350.2 1124.2 12.2 76.3 430.1 1115.8 14.2 79.4

[0050] Example 2

[0051] The sample with the size of Φ300×30mm was used and the β -40℃ for 1h, heated to Tβ+25℃ for 2~4h, cooled to room temperature, counted α grain size, then heated to 820~850℃ for (1~3)h and furnace cooled, furnace cooled, kept at 740~760℃ for (1~3)h and air cooled, kept at 600~620℃ for (2~6)h and air cooled to room temperature. The microstructure of TC18 titanium alloy obtained after two-step heat treatment is as follows: Figure 3 .

[0052] The α grain sizes corresponding to different holding times of the TC18 titanium alloy rod treated in this embodiment are shown in Table 3.

[0053] Table 3 α grain size corresponding to different holding time of TC18 rod in Example 2

[0054] Insulation time / h α Grain size / um 0.5h 208 1h 260 2h 300 4h 349 8h 440

[0055] The room temperature mechanical properties parameters corresponding to different α grain sizes of the TC18 titanium alloy rod treated in this embodiment are shown in Table 4.

[0056] Table 4 Room temperature mechanical properties of TC18 rods with different α grain sizes in Example 2

[0057]

[0058]

[0059] Example 3

[0060] The sample with the size of Φ300×30mm was used and the β -40℃ for 1 h, heated to Tβ+35℃ for 0~4h, cooled to room temperature, counted α grain size, then heated to 820~850℃ for (1~3)h and furnace cooled, furnace cooled, kept at 740~760℃ for (1~3)h and air cooled, kept at 600~620℃ for (2~6)h and air cooled to room temperature. The microstructure of TC18 titanium alloy obtained after two-step heat treatment is as follows: Figure 4 .

[0061] The α grain sizes corresponding to different holding times of the TC18 titanium alloy rod treated in this example are shown in Table 5.

[0062] Table 5 α grain size corresponding to different holding time of TC18 rod in Example 3

[0063] Insulation time / h α Grain size / um 0.5h 217 1h 245 2h 317 4h 362 8h 460

[0064] The room temperature mechanical properties parameters corresponding to different α grain sizes of the TC18 titanium alloy rod treated in this example are shown in Table 6.

[0065] Table 6 Room temperature mechanical properties of TC18 rods with different α grain sizes in Example 3

[0066] α Grain size / um Tensile strength / MPa Elongation / % Fracture toughness / Pa·m1 / 2 217 1102 13.2 74.2 245 1115 11.2 71.5 317 1128 10.8 75 362 1125 12.4 77 460 1110 14 80

[0067] Comparative Example

[0068] The comparative example is a specific implementation scheme of TC18 titanium alloy prepared by a traditional double annealing process.

[0069] A sample with a size of Φ300×30mm was used. After heating at 905℃ for 1.5h, it was uniaxially pressed down with a reduction of 45%. The double annealing heat treatment system was used for pressing down: heating to 820-850℃ and keeping it for (1-3)h, then furnace cooling, furnace cooling, keeping it for (1-3)h at 740-760℃, then air cooling, air cooling, keeping it for (2-6)h at 600-620℃, then air cooling to room temperature. The microstructure morphology of TC18 titanium alloy obtained after traditional double annealing heat treatment is as follows: Figure 5 .

[0070] The room temperature mechanical properties of TC18 titanium alloy bars after comparative heat treatment are shown in Table 7.

[0071] Table 7 Room temperature mechanical properties of TC18 rods in comparative examples

[0072] Tensile strength / MPa Elongation / % Fracture toughness / Pa·m1 / 2 1089 8.2 60.8

[0073] Comparing Examples 1-3 of the present invention with the comparative example, it can be seen from the microstructure morphology diagram that:

[0074] The size and content of the α phase in Examples 1-3 are greater than those in the comparative example. Figure 6 is the curve of TC18 titanium alloy grain size changing with unidirectional zone temperature and holding time; Figure 6 It can be seen that when the holding time is 0.5h, the single-phase region temperature has little effect on the grain size. As the holding time increases, the effect of the single-phase region temperature on the grain size gradually increases. The higher the single-phase region temperature, the more obvious the increase rate of the grain size.

[0075] From the mechanical properties, it can be found that the strength and fracture toughness of TC18 titanium alloy in the example are higher than those in the comparison example. Figure 7 , Figure 8 as well as Fig. 9 It can be seen that after double annealing, the tensile strength of TC18 titanium alloy rods increases first and then decreases with the increase of grain size, and the tensile strength is the highest when the grain size is 300μm. The change trends of fracture toughness and elongation are opposite, first decreasing and then increasing, and are lowest when the grain size is 300μm. Taking into account the contradictory relationship between tensile strength and fracture toughness and elongation, in order to make TC18 titanium alloy components have both high tensile strength and good plasticity and toughness, the grain size of TC18 titanium alloy rods is preferably controlled in the range of 300-430μm, and the corresponding single-phase zone temperature and holding time are preferably [Tβ+25℃, Tβ+35℃] and 2-4h, respectively.

[0076] The above examples prove that the service performance consistency heat treatment process method of the TC18 titanium alloy structure of the present invention is significantly better than the traditional double annealing heat treatment process method.

[0077] The embodiments described above are only descriptions of the preferred implementation modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.

Claims

1. A TC18 titanium alloy structure service performance consistency heat treatment process method, characterized in that: It includes the following steps: The first step of heat treatment: single-phase zone heating; TC18 titanium alloy is used as raw material. TC18 titanium alloy is a dual-phase titanium alloy composed of β phase and equiaxed α phase; The TC18 titanium alloy is kept at Tβ-40°C for 1 hour according to the air-fired heat treatment process, the temperature is raised to [Tβ+15°C, Tβ+35°C] and kept for 2 to 4 hours, and then cooled to room temperature, wherein Tβ is the phase transition temperature point of the β phase of the titanium alloy; The TC18 titanium alloy has an equiaxed α grain size of 200 to 430 μm after the first step heat treatment; The second step of heat treatment: double annealing; The cooled TC18 titanium alloy obtained by the first step heat treatment is heated to 820-850°C and kept at that temperature for 1-3 hours, then furnace cooled, kept at 740-760°C for 1-3 hours after furnace cooling, then air cooled, kept at 600-620°C for 2-6 hours after air cooling to room temperature.

2. A TC18 titanium alloy structure service performance consistency heat treatment process according to claim 1, characterized in that: The chemical composition of the TC18 titanium alloy is: Ti-5Al-5Mo-5V-1Cr-1Fe.

3. A TC18 titanium alloy structure service performance consistency heat treatment process according to claim 2, characterized in that: The TC18 titanium alloy has an equiaxed α phase volume fraction of 36% and an average size of 3 to 8 μm.

4. The TC18 titanium alloy microstructure and service performance consistency heat treatment process according to claim 1, characterized in that: The cooling method to room temperature in the first step of heat treatment is air cooling.

5. The TC18 titanium alloy microstructure and service performance consistency heat treatment process according to claim 1, characterized in that: The TC18 titanium alloy has an equiaxed α grain size of 300 to 430 μm after the first step heat treatment.

6. The TC18 titanium alloy microstructure and service performance consistency heat treatment process according to claim 1, characterized in that: The service properties include tensile strength, elongation and fracture toughness.

7. The TC18 titanium alloy microstructure and service performance consistency heat treatment process according to claim 1, characterized in that: The TC18 titanium alloy obtained after the second step of heat treatment has a tensile strength of 1110-1140 MPa, an elongation of 11-14%, and a fracture toughness of 70-80 MPa·m 1 / 2 .

Citation Information

Patent Citations

  • Thermal treatment method for TC18 titanium alloy

    CN103924180A

  • Heat treatment method for TC18 titanium alloy with high fracture toughness

    CN115725916A

  • Forging method for improving TC18 titanium alloy structure property

    CN105483586A

Cited By

  • A gradient cooling rate field controlled heat treatment process suitable for TC18 tube piercing

    CN120249857B